The Effect of Leadership and Motivation on Employee Performance at PT. Prima Lestari in Tangerang - Lia Asmalah; Zacharia Rialmi (Universitas Negeri Makassar, 2019)
Human resources play an important role in company management. The purpose of this study was to determine the effect of leadership and work motivation on employee performance at PT. Prima Lestari. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using a saturated sampling technique method with a sample of 95 respondents. The analysis tool uses a validity test, reliability test, classic assumption test, regression test, correlation test, coefficient of determination test and hypothesis test. The results of this study are that there is a positive and partially significant effect between leadership on employee performance at PT. Prima Lestari with a contribution of 32.6%, the hypothesis test obtained t count> ttable or (6,710> 1,986). Work motivation has a positive and significant effect on employee performance by 42%, the hypothesis test obtained tcount> ttable or (8.214> 1.986). There is a positive and significant effect between leadership and work motivation on employee performance with an influence contribution of 48.3% while the remaining 51.7% is influenced by other factors. Hypothesis testing test obtained Fcount> Ftable or (43.020) 2,700), it is also strengthened by a significance of 0,000 <0.05.